2017
DOI: 10.4103/2277-9175.205190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibular Fixation in the Treatment of Combined Distal Tibia and Fibula Fracture: A Randomized, Control Trial

Abstract: Background:This randomized, parallel-group, non-blinded study was designed to determine the role of fibular fixation in the treatment outcomes of combined distal tibia and fibula fractures.Materials and Methods:Sixty patients with distal tibial and fibular fractures were randomly divided in two groups of case and controls. In the case group, fibula was fixed prior to the fixation of tibia. In the control group, tibia was fixed without fibular fixation. Primary outcomes were varus–valgus angulation, anterior–po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The inclusion processes and reasons for exclusion are depicted in Figure 1 . Three [ 22 , 24 , 25 ] studies were randomized controlled trials, another three [ 20 , 21 , 26 ] of the seven were retrospective studies, and only one [ 23 ] was a prospective cohort study. All patients, both in the trial and control groups, were treated with interlocking IM nail or plate fixation for tibia fracture, and patients in the trial group additionally underwent fixation with a 3.5 mm dynamic compression plate (DCP) for fibula fracture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion processes and reasons for exclusion are depicted in Figure 1 . Three [ 22 , 24 , 25 ] studies were randomized controlled trials, another three [ 20 , 21 , 26 ] of the seven were retrospective studies, and only one [ 23 ] was a prospective cohort study. All patients, both in the trial and control groups, were treated with interlocking IM nail or plate fixation for tibia fracture, and patients in the trial group additionally underwent fixation with a 3.5 mm dynamic compression plate (DCP) for fibula fracture.…”
Section: Resultsmentioning
confidence: 99%
“…All patients, both in the trial and control groups, were treated with interlocking IM nail or plate fixation for tibia fracture, and patients in the trial group additionally underwent fixation with a 3.5 mm dynamic compression plate (DCP) for fibula fracture. Two studies [ 22 , 23 ] excluded patients with open fractures, leaving all patients included with closed fractures. All patients were followed up for more than 6 months (from 6 to 21 months) with valgus/varus and posterior/anterior angulations and nonunion, and the infection rates of most patients were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…However, some other studies found that standard open reduction and internal fixation of tibia with intramedullary nail or minimally invasive percutaneous plate osteosynthesis (MIPPO), without the fibula being fixed, had good reduction stability of tibial fracture, reduced the risk of soft tissue injury and infection, and had a good prognosis of function [ 7 9 ]. Javdan [ 10 ] reported that dynamic compression bone plate (DCP) or tubular plate fixation of fibula had no significant difference in influence on tibial fracture healing, reduction of postoperative complications and recovery of affected limb function. In addition, a few studies have shown that fibular plate internal fixation can increase the rate of delayed healing and non-healing of tibial fractures [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…e work in [10] compared biomechanically bionic, helical, and endobutton thread fixation during tibiofibular syndesmosis treatment. In present, there is no clear consensus on the optimum management of combined distal third tibia and fibula fractures [11][12][13].…”
Section: Introductionmentioning
confidence: 99%